Nanopalladium on polyethylenimine–grafted starch: An efficient and ecofriendly heterogeneous catalyst for Suzuki–Miyaura coupling and transfer hydrogenation reactions. (16th June 2017) - Fu, Lixia; Deng, Wenxiu; Liu, Lujie; Peng, Yanqing
Abstract : Functionalized natural polysaccharides are attractive supports for colloidal metal nanocatalysts due to their abundance, cheapness, biocompatibility and biodegradability. In this study, isocyanate–functionalized starch was prepared by treating with diisocyanate. Polyethylenimine grafted onto starch via the formation of urea linker. The palladium nanoparticles deposited starch PEIS@Pd(0) was obtained through a chelating– in situ reduction procedure. Characterization of these materials was done using Fourier transform infrared spectroscopy, scanning electron microscopy, transmission electron microscopy, X–ray diffraction, and inductive coupled plasma atomic emission spectrometry. The catalytic activity of PEIS@Pd(0) was then tested in two series of model reactions: Suzuki–Miyaura coupling and transfer hydrogenation. The catalyst could be recovered by simple filtration and was reused for five times without significant loss of catalytic activity, which confirmed the good stability of the catalyst. Abstract : Palladium nanoparticles were supported on polyethylenimine–grafted starch which could be employed as efficient, ecofriendly and reusable heterogeneous catalyst for Suzuki–Miyaura coupling and transfer hydrogenation.